One-Pot Synthesis of α,β-Unsaturated Esters Promoted by Sodium Hydride - Swetha, M.; Venkata Ramana, P.; Shirodkar, S.G. (Asian Journal of Chemistry, 2010)
A new protocol for the synthesis of α,β-unsaturated esters was described with various aldehydes and ethyl acetate in presence of sodium hydride. Advantage of this method is high efficiency, shorter time period and inexpensive.